Application of potassium fertilizer and plant growth regulators to the growth and productivity of purple sweet potato - Sulistyowati, Desty Dwi; Widiyono, Wahyu (Indonesian Journal of Applied Environmental Studies, 2023)
The study aimed to determine the effect of plant growth regulators and potassium fertilizer on the growth and productivity of three clones of purple sweet potato. The experiment was conducted at IPB University experimental station in Leuwikopo Dramaga Bogor for seven months. The study used a split-plot design with three factors and three replications. The first factor was as a subplot, namely plant growth regulators (PGR) application which consisted of two levels of without PGR (S0) and with PGR (S1) concentration of 2 cc l-1 of water (2,000 ppm). The second factor was as a subplot, namely rates of potassium chloride fertilizer (60, 120, 180 kg ha-1 K2O). The third factor as the main plot was sweet potato clones of (K1) Ayamurasaki, (K2) RIS-03063-05, and (K3) MSU 03028-10. The concentration of 2,000 ppm PGR did not significantly affect growth and tuber yield components. Potassium chloride K2O of 60 kg ha-1 up to 180 kg ha-1 did not significantly affect growth and tuber yield components. MSU 03028-10 clone had the highest total tuber yield (1537.8), healthy tuber (1529.9), unmarketable tuber (740.3), and small tuber (709.0). MSU 03028-10 clones have the longest stem length and the largest number of leaves 3-12 WAP. This study indicates that the MSU 03028-10 clone produces better growth and productivity than other clones.ABSTRAKPenelitian bertujuan untuk mengetahui pengaruh zat pengatur tumbuh dan pupuk kalium terhadap pertumbuhan dan produktivitas tiga klon ubi jalar ungu. Percobaan dilakukan di Kebun Percobaan IPB University di Leuwikopo Dramaga Bogor selama tujuh bulan. Penelitian menggunakan rancangan petak terbagi (split-plot design) dengan tiga faktor dan tiga ulangan. Faktor pertama sebagai anak petak yaitu pemberian zat pengatur tumbuh (PGR) yang terdiri dari dua taraf yaitu tanpa PGR (S0) dan dengan PGR (S1) konsentrasi 2 cc l-1 air (2.000 ppm). Faktor kedua sebagai anak petak yaitu takaran pupuk kalium klorida (60, 120, 180 kg ha-1 K2O). Faktor ketiga sebagai petak utama adalah klon ubi jalar (K1) Ayamurasaki, (K2) RIS-03063-05, dan (K3) MSU 03028-10. Konsentrasi PGR 2.000 ppm tidak berpengaruh nyata terhadap komponen pertumbuhan dan hasil umbi. Kalium klorida K2O ukuran 60 kg ha-1 sampai dengan 180 kg ha-1 tidak berpengaruh nyata terhadap komponen pertumbuhan dan hasil umbi. Klon MSU 03028-10 mempunyai hasil total umbi tertinggi (1537,8), umbi sehat (1529,9), umbi tidak layak jual (740,3), dan umbi kecil (709,0). Klon MSU 03028-10 mempunyai panjang batang terpanjang dan jumlah daun terbanyak 3-12 MST. Penelitian ini menunjukkan bahwa klon MSU 03028-10 menghasilkan pertumbuhan dan produktivitas yang lebih baik dibandingkan klon lainnya.